(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Dichlorvos Organophosphate Pesticide (DOP) is an occupational and environmental toxicant which has been classified as highly hazardous and carcinogenic. DOP has been associated with a number of immunocompromised effects as it interferes and interacts with the specific immunological functions. However, there is lack of information on the effects of DOP on serum cytokine levels in DOP users, thus, selected pro- and anti-inflammatory cytokines were therefore measured in adult male farmer workers exposed to DOP. Materials and Methods: One hundred and twenty adult male Farm Workers (FW) consisting of 60 Pesticide Applicators (PA) and 60 farmers exposed to DOP for not less than ten years were randomly enrolled into this study. Sixty apparently healthy adult males without occupational exposure to DOP served as controls. Serum levels of pro-inflammatory cytokines [tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ)] and anti-inflammatory cytokines [interleukins (IL)-4 and IL-10] were determined using ELISA. Data were analyzed using ANOVA, Post-Hoc and Pearson correlation coefficient. P-values less than 0.05 were considered as statistically significant. Results: The serum levels of IFN-γ and IL-4 were significantly higher in FW compared with the controls while the serum levels of IFN-γ, IL-4 and IL-10 were significantly higher in PA compared with the farmers. IL-4 had significant positive correlation with IFN-ϒ in farm workers, PA and farmers exposed to DOP but IL-4 had significant positive correlation with TNF-α in farmers only. Conclusion: There is a balanced pro and anti-inflammatory cytokine secretion in farm workers with long term exposure to DOP which regulates the pathogenicity of DOP exposure.